Nanomaterials for acute myeloid leukemia therapy: Current progress and future perspectives - Jiarui Zhao; Jiaqi Cui; Lixuan Wang; Xinyi Shi; Jiayan Ding; Muhammad Farhan Sohail; Irshad Hussain; Qihui Liu; Fangfang Chen (Interdisciplinary Medicine)
Abstract Acute myeloid leukemia (AML) is a highly aggressive hematologic malignancy characterized by poor prognosis, high relapse rates, and resistance to conventional chemotherapy. The limitations of standard treatments, including systemic toxicity and non‐specific drug distribution, highlight the need for novel therapeutic strategies. Nanoparticles (NPs) represent a promising approach for enhancing AML treatment by improving drug solubility, bioavailability, and targeted delivery while simultaneously minimizing adverse effects. Various NPs, including liposomes, polymeric micelles, dendrimers, carbon‐based, and metal NPs, have been explored for their ability to selectively target leukemic cells through passive and active targeting mechanisms. Functionalized NPs can exploit the enhanced permeability and retention effect for passive accumulation in leukemia‐affected tissues, while ligand‐modified NPs enable active targeting of AML‐specific biomarkers such as CD33, CD123, and folate receptors. Furthermore, NPs facilitate combination therapies, controlled drug release, and intracellular drug delivery, overcoming multidrug resistance and enhancing therapeutic efficacy. This review discusses the latest advancements in NP‐based AML therapies, their targeting strategies, and prospects for clinical translation, emphasizing the potential of nanotechnology in revolutionizing AML treatment.